Review of Predictions on the Number of Children Affected by Stunting in Mountainous Papua Using Differential Methods - Shella Puji Rahma Ayu, Shella (Jurnal Matematika dan Sains (JMS), 2024)
This study aims to analyze the relationship between various factors, such as family characteristics, eating patterns, and infection rates, as well as the incidence of stunting in children in the Papuan Mountains. The method used in this research is a qualitative bibliographic method. The differential equation model developed in this research uses historical trends and key factors to predict the number of stunting cases in 2024. This model combines the rate of change in factors that influence stunting with the current prevalence of stunting in a region. The model results show that the number of stunting cases is expected to increase based on the calculation results for an accuracy level of 25 and a MAPE of 88% in 2024. The differential equation model developed in this research provides a useful tool for policy makers and health professionals to predict and plan stunting management. in the Papuan highlands.